study of white blood cells changes in mice infested with gamma rays radiant and not radiant fertile protoscolices of echinococcus granulosus - Al-bayatee, Ahmad J.; Jawad, Shatha Q. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: